The Trial - Kafka, Franz,Mitchell, Mike,Robertson, Ritchie (Oxford University Press USA - OSO, 2009)
The Trial is one of the central works of modern literature. This meticulous new translation includes the chapters Kafka left incomplete and is accompanied by a biographical preface, detailed introduction, chronology, bibliography and notes. Intro – Contents – Biographical Preface – Introduction – Note on the Text – Select Bibliography – A Chronology of Franz Kafka – THE TRIAL – The Arrest – A Conversation with Frau Grubach: Then Fräulein Bürstner – The First Hearing – In the Empty Conference Hall: The Student: The Offices – The Thrasher – His Uncle: Leni – The Lawyer: The Factory-Owner: The Painter – Block, the Corn Merchant: The Dismissal of the Lawyer – In the Cathedral – The End – FRAGMENTS – B.'s Friend – The Lawyer from the State Prosecution Service – Going To See Elsa – The Fight with the Deputy Manager – The Building – Going To See His Mother – Explanatory Notes.
Description based on publisher supplied metadata and other sources
Keywords: Trials – Fiction; Electronic books